MORPHOLOGICAL AND PATHOGENIC VARIABILITY OF ALBUGO CANDIDA ISOLATES CAUSING WHITE RUST IN RAPESEEDMUSTARD - PANDEY, PUJA; A.K. TEWARI; R. P. AWASTHI (The Bioscan, 2013)
The present investigation was undertaken to study morphological and pathogenic variability of six Albugo candida isolates collected from Pantnagar, Ludhiana, Hisar, Bharatpur, Delhi, Kangra and Jammu. The morphological variability viz. shape, size and sporangial germination in different isolates was slightly different in different A. candida isolates . The shape of sporangia in Pantnagar isolate was slightly spherical; while it was globular in all other isolates. The size of sporangia in different isolates was ranged from 16.25 (Pantnagar) to 22.5 μm (Bharatpur). The sporangial germination varied from 74.63(Hisar) to 90.04 per cent (Pantnagar). The pathogenic variability viz. pustule size , shape, incubation period, inoculation period and disease index was also varied in A. candida isolates. The small size pustules (0.5-1.5 mm) was observed in New Delhi and Hisar isolates, while large size pustules (1-3 mm) in Pantnagar and Ludhiana isolates. Pinhead raised pustules was observed in Pantnagar, Delhi, Bharatpur, Hisar, Kangra and Jammu isolates, while pinhead scattered pustules in Ludhiana isolates. At cotyledonary stage A. candida isolates showed variation in incubation period (IP) ranged from 4-9 days and latent period (LP) from 9-12 days. Maximum mean disease index was in Pantnagar isolate (22.27%), while minimum was observed Delhi isolate (15.87 %).